LA PACE E LA GIUSTIZIA COME “DIRITTI ESSENZIALI” DELL’UOMO - Parente, Ferdinando (Civitas et Lex, 2018)
The link between peace and justice, in the system of sources of Italian law is often expressed through the two antithetic categories, namely the idea of war and the concept of social injustice. In fact, the Constitution sometimes makes a direct reference to peace; other times, recalls the peace in an indirect way, through its opposite, war, that repudiates firmly. In the history of humanity, the issues of social injustice have been contributory causes expressions of dissatisfaction, in the face of existential human rights ignored, injury and lack of respect for the dignity of the person. Therefore, the phenomenon of peace has become more not only a legal but also economic, ethical and social importance. In this perspective, the right to peace and the right to social justice may be included among the essential rights of man, worthy of absolute protection and unconditional.